EFEKTIVITAS PROGRAM PEMBELAJARAN DARING MATA PELAJARAN EKONOMI - Eko Putro Widoyoko; Cahyo Apri Setiaji; Gita Tiara; Arum Melinawati (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This study aims to determine the effectiveness of the online learning program for economics subjects in high schools in Kebumen Regency for the academic year 2021/2022. The research employs an evaluation research design using quantitative methods. Data collection methods include questionnaires and document analysis. Data analysis was conducted using descriptive analysis. The results of the study indicate that, on average, the online learning program for economics subjects in high schools in Kebumen Regency has been effectively implemented. The quality of economics learning in public high schools is better (mean = 2.98) compared to private high schools (mean = 2.96). The learning output in public high schools is higher (mean = 80.41) compared to private high schools (mean = 79.61). The effectiveness of the learning program in public high schools (mean = 2.91) is better compared to private high schools (mean = 2.86). The differences in the effectiveness of the learning program implementation between public and private high schools are partly due to differences in student input, teacher quality, and online learning facilities.